The relationship between water quality measurements and the prevalence of kidney dysfunction among HTI employees in Banyuasin, Indonesia - Sulistya Ningsih; Marthia Ikhlasiah (Priviet Social Sciences Journal, 2026)
Chronic Kidney Disease (CKD) is a global health challenge with a worldwide prevalence of 13,4%. (Riskesdas, 2018). In. Indonesia, while the national prevalence among the productive-age population is 0,38%, Industrial Forest Plantation or Hutan Tanaman Industri (HTI) employees in Banyuasin are at increased risk due to exposure to substandard drinking water with acidic pH (mean 5.8 ± 0.4), heavy metals (Fe 0.45 mg/L), Total Dissolved Solids (TDS) of 420 mg/L, and extreme occupational heat stress (38.2 °C). This study aimed to analyze the relationship between water quality parameters and kidney dysfunction among HTI employees and to identify occupational risk factors that exacerbate renal health in industrial settings. This narrative review, conducted in April 2026, synthesized evidence from 10 studies published between 2018 and 2026. A systematic literature search was performed via PubMed, Scopus, Sinta, and Google Scholar using keywords such as “water quality,” “pH nephrotoxicity,” and “occupational CKD,” occupational CKD. This review focused on the correlation between water quality parameters (pH, TDS, and contaminants) and clinical renal dysfunction indicators (estimated Glomerular Filtration Rate (eGFR) and creatinine) among industrial workers based on medical check-up data, with a focus on the implications for HTI Banyuasin, Indonesia. The literature synthesis demonstrated that contamination of drinking water by Perfluorooctanoic Acid (PFOA) and heavy metals is significantly associated with a decline in the eGFR. Furthermore, chronic dehydration resulting from heat stress in tropical environments induces recurrent Acute Kidney Injury (AKI), which contributes to the development of Chronic Kidney Disease of unknown (CDKu) etiology. Poor water quality and inadequate hydration management are major risk factors for kidney disorders among HTI employees. Strengthening workplace Water, Sanitation, and Hygiene (WASH) standards is essential for the early prevention and long-term protection of worker health.